Efficient array design algorithm for wide-band application of the MUltiple SIgnal Classification algorithm - Takada, Jun-ichi; Desoki, Ahmed; Hagiwara, Ichiro (Acoustical Science and Technology, 2009)
This paper analyzes the error in MUSIC results due to the effect of finite precision arithmetic. Thus, relation of this error to sources correlation level and array and sources configuration parameters is clearly identified. As a result efficient array design algorithm suitable for acoustic environments is derived. This algorithm is efficient in the sense that it can determine minimum number of sensors. This algorithm is quite general as it includes the effect of all parameters such as number of sources, sources correlation level, maximum resolution, maximum source angle, number of sensors, sensor spacing and arithmetic precision. Also this algorithm is shown to be seamlessly applicable in realistic environments where many additional effects and sources of error often exist. During this paper it is shown that this algorithm is indispensable for DOA estimation in wide-band and reverberant environments.